Structural and the Optical Properties of Graphene Prepared by Electrochemical Exfoliation Technique. - Jibrael, Raneen Imad; Mohammed, Mustafa K A (Al-Nahrain Journal of Science, 2018)
In this research, graphene suspension was prepared by electrochemical exfoliation of graphite electrodes immersed in aqueous solution which contains sulfuric acid, nitric acid and distilled water (H2SO4/HNO3/H2O). DC biases of 10 V have been applied and the graphene foam was deposited on glass slide. The structural and optical properties of graphene was characterized via X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive spectroscopy (EDS), optical microscopy (OP) and Uv-Vis spectroscopy respectively. The XRD pattern shows crystalline structure of graphene with sharp peak at 26.59o corresponds to an interlayer distance of 0.334 nm of (002) orientation which matching with the interlayer distance of normal graphite. The SEM of graphene was showed that thin layered graphene structures with wrinkled shapes. The compositions of graphene consist of carbon and oxygen with atomic percentages 82.75% and 12.01%, respectively. The absorbance spectra using UV-VIS was exibited the graphene suspension and graphene film have two transitions included π-π* and n- π* respectively.